Utilization of Food Plant by Sundanese Ethnic, in Nyangkewok Hamlet, Sukabumi Regency: PEMANFAATAN TUMBUHAN PANGAN OLEH ETNIK SUNDA, DI KAMPUNG NYANGKEWOK, KABUPATEN SUKABUMI - Cita, Ken Dara; Hasibuan, Ratna Sari (Media Konservasi, 2019)
Food sovereignty has become a crucial problem for mankind. Sukabumi Regency is one of the regions that has been experienced a food crisis. The people of Nyangkewok Village, Sukabumi Regency have local knowledge in the use of food plants which can be an alternative in overcoming food insecurity. This research aimed to identify and describe the utilization of food plants by local knowledge of Sundanese Ethnic in Nyangkewok Hamlet, Sukabumi. The research was conducted in March-June 2019 with qualitative and qualitative methods, with data collection techniques by field observations and respondents interview. The results showed that there was a decline trend in the knowledge of using local food, in the lifestyle of the younger generation. Local knowledge tends to decrease from the older generation to the younger generation. There are 101 types of food plants that are utilized by local Sundanese people in Nyangkewok village with the dominant family type is Cucurbitae. There was a traditional ceremony which was "Mitembeyan" as a form of offering ceremony to Dewi Sri (Nyi Pohaci) who is believed to be the giver of crop fertility. Keywords: conservation, food plant, food security, local knowledge, Sundanese ethnic